ANALISA KONSENTRASI TERHADAP PERFORMA SHOOTING ATLET PETANQUE BINAAN KONI ACEH - Isdarianti, Novi Lidya; Masri, Masri; Karimuddin, Karimuddin; Santoso, Nurhadi; Wiyanto, Agus (YLPK Mahardhika, 2024)
Concentration is believed to greatly affect performance in shooting in the sport of pétanque. Good concentration will be able to create points in shooting, thereby achieving optimal performance to attain victory. The research aims to analyze the concentration of shooting performance in the sport of petanque. A quantitative approach was taken to understand and address the existing issues. Total sampling was conducted involving a population of 11 players. The data collection technique was carried out through several stages: (1) concentration measured through the Grid Concentration test, and (2) shooting accuracy measured using the shooting ability test at a distance of 8.5 meters. The research results show that concentration significantly impacts shooting performance (r = 0.62), with concentration contributing 38.44% to shooting accuracy. Good concentration will have a significant impact on shooting performance, so concentration also requires a training process for its management.